2019
DOI: 10.1002/joc.6409
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary influence of the North Atlantic tropical cyclones on the spatio‐temporal variability of the eastern United States precipitation extremes

Abstract: In the eastern United States, the empirical probability distribution of extreme daily precipitation comprises heavy rainfall events stemming from North Atlantic tropical cyclones (TCs). At many locations, these events influence estimates of extreme value statistics (e.g., 100‐year event), thus have important bearing on the sizing of flood protection infrastructure and, in general, flood risk management and preparedness. Consequently, a characterization of location specific and regional patterns in precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In addition to this, it was observed that seasonal modes of AMF dates have weakened over time for a number of sites along the coastal region with the emergence of significant modes during late spring and early summer (May-June) as well as fall season (mid-September-November). The reason for the emergence of seasonality modes during the month of November along the coastal sites might be due to an increase in the heavy precipitation trends associated with tropical cyclones in the North Atlantic basins over the last 30 years [26,[40][41][42][43]. Similarly, the emergence of modes during the months of May and early June might be due to the emergence of extreme precipitation seasonality modes during late spring and early summer season for the latest time period as shown by Dhakal et al [25].…”
mentioning
confidence: 87%
“…In addition to this, it was observed that seasonal modes of AMF dates have weakened over time for a number of sites along the coastal region with the emergence of significant modes during late spring and early summer (May-June) as well as fall season (mid-September-November). The reason for the emergence of seasonality modes during the month of November along the coastal sites might be due to an increase in the heavy precipitation trends associated with tropical cyclones in the North Atlantic basins over the last 30 years [26,[40][41][42][43]. Similarly, the emergence of modes during the months of May and early June might be due to the emergence of extreme precipitation seasonality modes during late spring and early summer season for the latest time period as shown by Dhakal et al [25].…”
mentioning
confidence: 87%
“…By not accounting for these patterns, current methods for hydrologic design of infrastructure, such as flood frequency analysis and regional regression, are poorly suited for considering risk from nonstationarity of extreme events (Wright et al, 2019). In addition, extreme flooding events are increasingly being attributed to hurricanes (Dhakal & Jain, 2019), which presents challenges for flood frequency statistics in coastal regions. Therefore, alternative approaches to flood frequency are needed to consider the influence of peak flows from climate enlarged hurricanes.…”
Section: Introductionmentioning
confidence: 99%